Mineralogical characterization of calcium phosphate cements for clinical needs - Götz-Neunhoeffer, Friedlinde; Hurle, Katrin (Multiscale Cell-Biomaterials Interplay in Musculoskeletal Tissue Engineering and Regenerative Medicine, 2023)
Upon mixing of calcium phosphate cements (CPCs) with an aqueous liquid, the hydration starts. This dissolution–precipitation reaction is resulting in H2O-containing CaP phases. Mineralogical characterization of both processes can be easily performed by quantitative X-ray powder diffraction (XRD) analysis and heat-flow analysis. Rietveld refinement of XRD data is a very powerful tool for investigation of solid solutions in ion-doped CPCs and the time-dependent formation of apatite or brushite. G-factor allows quantification of the amorphous content, either of the anhydrous powder or in the hydrated pastes. For successful application of CPCs, properties of both paste and hardened cements must be carefully adjusted to meet clinical requirements. For proper application, injectability, cohesion, and setting time of the pastes are highly relevant. The hardened cement must allow proper degradation, which is related to both phase composition and porosity. Finally, the optimization of mechanical strength by polymeric additives needs to be monitored by the described setup of the methods.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Analytical method; Calcium phosphate cement; Crystallinity; Crystallography; External standard method; Hydroxyapatite; Isothermal calorimetry; Mineralogy; Quantitative X-ray diffraction; Setting reaction